Melejitkan Hasil Belajar Peserta Didik pada Mata Pelajaran Ilmu Pengetahuan Sosial melalui Metode Jigsaw - Kasiono, Trans (Lentera: Jurnal Ilmiah Kependidikan, 2023)
The research aimed to improve the students’ outcome in Social Science subject through Jigsaw. The subjects of this research were the grade IX students of class IX B at SMP Negeri 30 Bandarlampung year 2018/2019. Therefore, the classroom action research by using the Jigsaw model was conducted. This classroom action research consisted of 3 cycles. The subject of the research was 27 students from class IX B. The data of students’ activity level was obtained from the observation sheet and the result of students group work assignment. The data of student’s learning outcome was obtained from individual written evaluation. The research showed that there was an increase in students’ activity level and learning outcome from cycle I through cycle III. Those result proved that through Jigsaw model, the learning outcomes in Social Science subject of students in class IX B at SMP Negeri 30 Bandarlampung year 2018/2019 significantly increased.